2009
DOI: 10.1027/1016-9040.14.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Health-Related Outcomes of Collective Trauma

Abstract: The objective of our study was to systematically review research evidence for relationships between self-efficacy beliefs and psychological as well as somatic outcomes of collective traumatic events. Twenty-seven studies enrolling adult and adolescent survivors of acute, escalating, and chronic collective trauma with a total of N = 8011 participants were reviewed. Cross-sectional studies suggest medium to large effects of self-efficacy on general distress, severity and frequency of PTSD (posttraumatic stress d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
184
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(215 citation statements)
references
References 43 publications
21
184
2
1
Order By: Relevance
“…Where neighborly behavior may be a proxy for social support and social networks, this finding supports existing literature that social networks promote collective efficacy and that these networks are influential in the aftermath of a disaster (Kaniasty & Norris, 1993;Luszczynska, Benight, & Cieslak, 2009). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Where neighborly behavior may be a proxy for social support and social networks, this finding supports existing literature that social networks promote collective efficacy and that these networks are influential in the aftermath of a disaster (Kaniasty & Norris, 1993;Luszczynska, Benight, & Cieslak, 2009). …”
Section: Discussionsupporting
confidence: 84%
“…Subsequent research should address some of the limitations of this study by better measuring the link between social networks, changes in social networks after a disaster and how this impacts perceptions of the community as a whole including perceived collective efficacy. Luszczynska et al (2009), as well as Kaniasty and Norris (1993), suggest that changes in social support after a disaster have the potential to decrease perceived collective efficacy. Luszczynska et al also suggests that perceived collective efficacy after a disaster is highest for those who are able to accept social support networks immediately after the disaster has occurred.…”
Section: Future Directionsmentioning
confidence: 99%
“…A meta-analysis [11] demonstrated that higher coping self-efficacy, levels were consistently associated with lower levels of distress and posttraumatic stress symptom (PTSS) levels in cross-sectional and longitudinal studies.…”
Section: Copingmentioning
confidence: 99%
“…The high level of general selfefficacy may have served as a protective buffer between past psychological abuse and specific self-efficacy. Past studies of survivors of diverse traumas have reported that both general and specific self-efficacy can be protective against the development and severity ofPTSD symptoms (Benight & Bandura, 2004;Heinrichs et at, 2005;Luszczynska, Benight, & Cieslak, 2009), self-reported somatic symptoms, self-reported physical health disability, number of chronic diseases, and quality of chronic disease self-care (Barry et aI., 2003;Luszczynska, Benight, & Cieslak, 2009). In IPV survivors specifically, high specific self-efficacy is protective via its relationship with initiating and maintaining independence from an abusive or violent partner (Burke et aI., 2004;Lerner & Kennedy, 2000;Patzel, 2001), as well as a reduced risk for attempting suicide (Meadows et aI., 2005;Thompson et aI., 2002).…”
Section: Restriction Of Rangementioning
confidence: 99%
“…PTSD is a mental health disorder experienced by some trauma survivors and characterized by symptoms of hyperarousal, avoidance of trauma reminders, and involuntary re-experiencing of the traumatic event (American Psychiatric Association, 2000). Studies revealed that both general and specific self-efficacy are associated with the presence (Benight & Bandura, 2004) and severity ofPTSD symptoms (Luszczynska, Benight, & Cieslak, 2009). For example, in a prospective study of male firefighters, low general self-efficacy and high hostility immediately following basic training were strongly associated with the severity 2 ofPTSD symptoms two years later (Heinrichs et at, 2005).…”
Section: Self-efficacy and Post-trauma Outcomesmentioning
confidence: 99%